Fraction Addition and Subtraction

Easy

Medium

Difficult

Q1) \(\frac{2}{9}\) + \(\frac{5}{7}\) =
Q1) \(\frac{6}{7}\) - \(\frac{3}{5}\) =
Q1) 2\(\frac{1}{6}\) - 1\(\frac{3}{5}\) =
Q2) \(\frac{1}{2}\) + \(\frac{2}{5}\) =
Q2) \(\frac{4}{7}\) - \(\frac{1}{2}\) =
Q2) 2\(\frac{1}{2}\) + 1\(\frac{2}{7}\) =
Q3) \(\frac{4}{9}\) + \(\frac{1}{2}\) =
Q3) \(\frac{2}{3}\) - \(\frac{1}{2}\) =
Q3) 3\(\frac{1}{3}\) + 1\(\frac{2}{3}\) =
Q4) \(\frac{3}{10}\) + \(\frac{2}{9}\) =
Q4) \(\frac{8}{9}\) - \(\frac{2}{3}\) =
Q4) 1\(\frac{2}{5}\) + 1\(\frac{1}{2}\) =
Q5) \(\frac{1}{3}\) + \(\frac{1}{2}\) =
Q5) \(\frac{5}{6}\) - \(\frac{2}{5}\) =
Q5) 1\(\frac{1}{6}\) + 1\(\frac{3}{7}\) =
Q6) \(\frac{1}{4}\) + \(\frac{4}{9}\) =
Q6) \(\frac{5}{6}\) - \(\frac{1}{2}\) =
Q6) 2\(\frac{1}{2}\) - 1\(\frac{2}{3}\) =
Q7) \(\frac{2}{7}\) + \(\frac{4}{9}\) =
Q7) \(\frac{4}{5}\) - \(\frac{3}{8}\) =
Q7) 2\(\frac{3}{4}\) - 1\(\frac{1}{2}\) =
Q8) \(\frac{1}{3}\) + \(\frac{1}{2}\) =
Q8) \(\frac{4}{5}\) - \(\frac{1}{4}\) =
Q8) 1\(\frac{3}{5}\) + 3\(\frac{1}{3}\) =
Q9) \(\frac{5}{8}\) + \(\frac{2}{7}\) =
Q9) \(\frac{7}{9}\) - \(\frac{1}{2}\) =
Q9) 1\(\frac{3}{4}\) + 3\(\frac{1}{2}\) =
Q10) \(\frac{1}{5}\) + \(\frac{2}{5}\) =
Q10) \(\frac{6}{7}\) - \(\frac{2}{7}\) =
Q10) 4\(\frac{1}{3}\) - 2\(\frac{1}{4}\) =